Semantics of verbs of movement with the seme ‘down’ in Russian and German languages - Ustimenko, Elena G. (Journal of the Belarusian State University. Philology, 2023)
The article deals with the semantics of non-prefixed intransitive verbs denoting downward movement in Russian and German languages. Quantitative asymmetry of these verbs has been established. It has been found that the information about the medium, the nature of the moving object, the characteristics of the movement process and the end point of movement is common to their semantics. The differences are established in the number of types of information presented in the semantics of one verb, as well as in the directions of modifications of semantic features representing the detected types of information.